Des expériences comiques : l’esprit scientifique et la médecine dans Bouvard et Pécuchet - Niklas Bender (Flaubert: Revue Critique et Génétique)
A widely spread opinion holds that Bouvard et Pécuchet presents a violent critique of scientific discourse, that the novel deconstructs all scientific knowledge, and even Science itself. This paper tries to qualify this stereotype: by analyzing the medical episode of the novel, focusing especially on experimental physiology, it shows the way Flaubert develops a particular « comique d’idées ». The latter is obviously critical of scientific claims and contradictions, while remaining faithful to some basic principles of scientific discourse.